Developing A Hierarchical Framework for Selecting E-Commerce Platform for SMEs: An AHP Approach Based on Operational Perspective and Digital Readiness - Haunan Damar; Pradana Jati Kusuma; Bobur Sobirov (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2026)
Digital transformation among Indonesia’s Micro, Small, and Medium Enterprises (MSMEs) still faces challenges. Out of 64 million MSMEs, only 24% have adapted to digital business practices. MSMEs can transform digitally through online sales channels using the marketplace, however, many small business owners struggle to select the most suitable e-commerce platform for their business. In many cases, platform selection is influenced by popularity or promotional exposure rather than objective evaluation. This study aims at helping MSMEs select the most suitable e-commerce platform through operational and digital readiness criteria using Analytical Hierarchical Process (AHP). The framework integrates two major perspectives relevant to digital adoption, namely operational perspective and digital readiness. Data were gathered from 15 business owners who have experience using the most popular e-commerce platforms in Indonesia. Through pairwise comparison questionnaires and Saaty’s nine-point scale, evaluation criteria were examined including cost efficiency, platform functionality, ease of use, digital capability and operational support. The results indicate that cost efficiency is the most influential criterion (54.7%), followed by platform functionality (17.2%), operational support (15.4%), digital capability (9.5%) and lastly, ease of use (3.2%). The study was done to analyze four of the most popular e-commerce platforms in Indonesia namely Shopee, Tokopedia, Bukalapak and Lazada. The finding helps to propose a practical framework for small businesses to evaluate e-commerce platforms and support sustainable digital transformation initiatives.